2022
DOI: 10.3390/ijms23031252
|View full text |Cite
|
Sign up to set email alerts
|

Triptolide Suppresses NF-κB-Mediated Inflammatory Responses and Activates Expression of Nrf2-Mediated Antioxidant Genes to Alleviate Caerulein-Induced Acute Pancreatitis

Abstract: Triptolide (TP), the main active ingredient of Tripterygium wilfordii Hook.f., displays potent anti-inflammatory, antioxidant, and antiproliferative activities. In the present study, the effect of TP on acute pancreatitis and the underlying mechanisms of the disease were investigated using a caerulein-induced animal model of acute pancreatitis (AP) and an in vitro cell model. In vivo, pretreatment with TP notably ameliorated pancreatic damage, shown as the improvement in serum amylase and lipase levels and pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 36 publications
(41 reference statements)
2
11
0
Order By: Relevance
“…Considering that pharmacologic intervention against oxidative stress damage might be beneficial in delaying onset or progression of several diseases (Drake et al, 2003), we also compared the MDA levels in this study. consistent with previous studies (Yang et al, 2022), in our present study, SAP induced a significant elevation of MPO activity and MDA levels in experimental rats. Importantly, DCP treatment restored the pro-/anti-inflammatory balance, decreased MPO activity in the duodenum, colon, and cardiac tissues, and particularly increased MDA levels in the duodenum of rats with SAP, revealing a regulatory role of DCP in inflammatory responses and oxidative stress in Nat-induced SAP rats.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Considering that pharmacologic intervention against oxidative stress damage might be beneficial in delaying onset or progression of several diseases (Drake et al, 2003), we also compared the MDA levels in this study. consistent with previous studies (Yang et al, 2022), in our present study, SAP induced a significant elevation of MPO activity and MDA levels in experimental rats. Importantly, DCP treatment restored the pro-/anti-inflammatory balance, decreased MPO activity in the duodenum, colon, and cardiac tissues, and particularly increased MDA levels in the duodenum of rats with SAP, revealing a regulatory role of DCP in inflammatory responses and oxidative stress in Nat-induced SAP rats.…”
Section: Discussionsupporting
confidence: 94%
“…Accumulating evidence has shown that the Nrf2/HO-1 pathway is involved in the inflammatory response to AP. Yang et al reported that triptolide exerted a therapeutic role in cerulein-induced AP by activating the expression of Nrf2 and HO-1 in vivo and in vitro ( Yang et al, 2022 ). Liu et al found that antibody neutralization of HMGB1 decreased the intestinal injury score, MPO activity, and levels of TNF-α and IL-6 in an intestinal I/R injury mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…29 Similarly, triptolide, the main active ingredient of Tripterygium wilfordii Hook.f., is a newly defined NF-κB inhibitor that can alleviate Caerulein-induced acute pancreatitis. 30 The pro-inflammatory effect of SiNPs is tightly associated with the upregulated cytokines such as IL-1β, IL-6, and IL-18, which are all potential downstream targets of NK-κB. Here, we found consistent upregulation of IL-1β with NF-κB after SiNPs exposure, and the upregulation of IL-1β can also be inhibited by NF-κB inhibitor, suggesting the casual association between NF-κB and IL-1β.…”
Section: Discussionsupporting
confidence: 53%
“…By targeting the NF‐κB and MAPK signaling pathways, the Terminalia chebula fruits‐derived hydrolyzable tannin fraction shows an antiinflammatory effect on LPS‐stimulated RAW 264.7 cells 29 . Similarly, triptolide, the main active ingredient of Tripterygium wilfordii Hook.f ., is a newly defined NF‐κB inhibitor that can alleviate Caerulein‐induced acute pancreatitis 30 …”
Section: Discussionmentioning
confidence: 99%
“…Triptolide ( Figure 1 ), a major component of TwHF, has many beneficial functions, including immunosuppression, anti-inflammation, and anticarcinogenesis. The pharmacological influence of triptolide towards clinical progress showcases its role in different anti-inflammatory, immunomodulatory, antioxidant, and antiproliferation activities ( Tang et al, 2020 ; Tong et al, 2021 ; Yu et al, 2021 ; Yang et al, 2022 ). Furthermore, triptolide has been reported to play a critical role in various maladies, such as neurological disorders, respiratory illness, gastrointestinal disorders, renal diseases, endocrine diseases, autoimmune disorders, bone dysfunction, and cancer ( Yuan et al, 2019 ; Cheng et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%